2009
DOI: 10.4260/bjft2009200800004
|View full text |Cite
|
Sign up to set email alerts
|

A Influência Do Uso De Soro De Queijo E Bactérias Probióticas Nas Propriedades De Bebidas Lácteas Fermentadas

Abstract: ResumoBebidas lácteas fermentadas contendo bactérias probióticas foram elaboradas com 50, 40 e 30% de soro de queijo, e denominadas de bebida láctea 1, 2 e 3, respectivamente. Após a avaliação destas bebidas, verificou-se que as contagens de células probióticas não foram influenciadas pela proporção de soro, podendo também ser classificadas como probióticas. Quanto menor a proporção de soro de queijo utilizada nas bebidas, maiores os teores de sólidos totais (p < 0,05) e valores calóricos encontrados (p < 0,05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
0
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
2
0
1
4
Order By: Relevance
“…The caloric value (CV) followed the same tendency, with lower values for soymilk treatments. Similar results were found in fermented dairy beverages (63.9 to 79.3 Kcal 100g -1 ), with higher CV for treatments with higher cow milk ratio and lower CV for samples with higher whey content (Cunha et al, 2009). …”
Section: Chemical and Physicochemical Evaluationsupporting
confidence: 78%
“…The caloric value (CV) followed the same tendency, with lower values for soymilk treatments. Similar results were found in fermented dairy beverages (63.9 to 79.3 Kcal 100g -1 ), with higher CV for treatments with higher cow milk ratio and lower CV for samples with higher whey content (Cunha et al, 2009). …”
Section: Chemical and Physicochemical Evaluationsupporting
confidence: 78%
“…milk, that is, 0.6-2.0% lactic acid or 60-200°D (Brasil 2007). These values are similar to the ones obtained by Almeida et al (2001), Cunha et al (2009) and Penna et al (2003) for fermented whey and milk-based beverages with 30% whey addition. These authors found pH from 4.02 to 4.63 and acidity from 0.50% to 0.72% lactic acid.…”
Section: Figuresupporting
confidence: 89%
“…Castro et al (2009) observed slightly higher acidity (0.72-0.86% lactic acid). The viscosity values verified in this study are higher than the 0.263 and 0.026 Pa s found by Oliveira et al (2002) and Cunha et al (2009), respectively, and lower than the 3.1 Pa s obtained by Almeida et al (2001).…”
Section: Figurecontrasting
confidence: 76%
“…Entretanto, Barreto et al 32 ao avaliar os leites fermentados com L. acidophilus comercializados no Brasil verificaram contagens variando de 6,66 a 8,60 log UFC/g de produto. Cunha et al 33 encontraram valores para contagem de bactérias probióticas inferiores aos obtidos na presente pesquisa, correspondentes de 1,7x10 6 (6,2 log) a 9,8x10 6 (6,9 log) UFC/g durante 28 dias de estocagem e concluíram que a variação foi dependente da matéria prima utilizada na elaboração do leite fermentado e não do tempo de armazenamento a 5°C. Por sua vez, Gonçalves e Eberle 34 deduziram que a acidificação do produto final, os ácidos produzidos durante o armazenamento, o nível de oxigênio no produto e a permeação do oxigênio através da embalagem podem reduzir a viabilidade das culturas probióticas.…”
Section: C= Control Sample (L Acidophilus); I1= Indicator Sample 1 (unclassified